2016
DOI: 10.5424/fs/2016252-08021
|View full text |Cite
|
Sign up to set email alerts
|

A forest simulation approach using weighted Voronoi diagrams. An application to Mediterranean fir Abies pinsapo Boiss stands

Abstract: Aim of study: a) To present a new version of the forest simulator Vorest, an individual-based spatially explicit model that uses weighted Voronoi diagrams to simulate the natural dynamics of forest stands with closed canopies. b) To apply the model to the current dynamics of a Grazalema pinsapo stand to identify the nature of its competition regime and the stagnation risks it is currently facing.Area of study: Sierra del Pinar de Grazalema (S Spain) Material and methods: Two large plots representative of Graza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…Abies pinsapo is an endangered relict fir, which in the course of the twentieth century has suffered afforestation in some areas (Álvarez 2013), as the management of stands is leading to a process of mortality (Abellanas et al 2016). Abies pinsapo shares with Q. canariensis both a high demand for water and a restricted distribution, and consequently follows a similar trend to the latter in our LR model, although with more drastic consequences.…”
Section: Modelling Conifer Forest Dynamicsmentioning
confidence: 64%
“…Abies pinsapo is an endangered relict fir, which in the course of the twentieth century has suffered afforestation in some areas (Álvarez 2013), as the management of stands is leading to a process of mortality (Abellanas et al 2016). Abies pinsapo shares with Q. canariensis both a high demand for water and a restricted distribution, and consequently follows a similar trend to the latter in our LR model, although with more drastic consequences.…”
Section: Modelling Conifer Forest Dynamicsmentioning
confidence: 64%
“…En este mismo periodo, se han sucedido años húmedos y años secos, y, de hecho, los últimos años se corresponden con un periodo seco. En el caso de la Sierra de Grazalema, el hecho de que la tendencia no fuera significativa permite inferir que estamos ante un pinsapar muy denso, maduro y estable (Arista, 1995;Abellanas et al, 2016).…”
Section: Discussionunclassified
“…The results of grey correlation analyses of the number of trees adjacent to the central tree and its key in uencing factors showed that the average crown width of conifer-broadleaved mixed forests at each thinning intensity (10%, 15%, 20%, 25%, 30%, 35%) had a greater in uence on the spatial extent of structure units when compared to the control forest plot; the crown length factor had higher in uence than the tree height. It has been shown that the allocation of tree organs is strongly related to spatial partitioning and that tree growth grows with the acquisition of canopy space (Abellanas et al, 2016a;Goudie et al, 2009;Moeur, 1993). Our ndings thus provide a theoretical basis for the scienti c determination of the structure units of nurtured mixed conifer-broadleaved forests.…”
Section: Discussionmentioning
confidence: 99%
“…Both methods have shortcomings which are compensated for by using the non-spatial structure parameters of the stand as weights. The in uence of the diameter at breast height is strong and is thus used to weight the spatial structure units (Aakala et al, 2013;Li et al, 2015), and this has developed into a weighting analysis using tree height, diameter at breast height, and crown (Abellanas et al, 2016b;. This study modi es this weighting analysis by not only adding the crown length attribute to those of diameter at breast height, height, and crown spacing but also making reasonable usage of the crown and stand spacing factors that are related to stand density based on the characteristics of the species in the mixed forests.…”
Section: Introductionmentioning
confidence: 99%